Six lessons about mathematical education in times of change: didactical itineraries to learn more and better (Journal of Parents and Teachers, 2018)
Traditionally, school mathematics has been presented as an abstract knowledge that is learned through repetition and practice: how many more exercises, better learning! Nothing could be more untrue: mechanics helps to memorize but not to understand or use mathematical knowledge effectively. The article proposes a respectful vision with the real needs of children to learn mathematics: an itinerary that includes daily situations, manipulative materials, games, literary, technological and graphics resources and guidance for parents and teachers are proposed.
Keywords: mathematics education; mathematical literacy; teaching-learning contexts; early childhood education; primary education